2010
DOI: 10.1128/aem.02670-09
|View full text |Cite
|
Sign up to set email alerts
|

Improved Strains and Plasmid Vectors for Conditional Overexpression of His-Tagged Proteins in Haloferax volcanii

Abstract: Research into archaea will not achieve its full potential until systems are in place to carry out genetics and biochemistry in the same species. Haloferax volcanii is widely regarded as the best-equipped organism for archaeal genetics, but the development of tools for the expression and purification of H. volcanii proteins has been neglected. We have developed a series of plasmid vectors and host strains for conditional overexpression of halophilic proteins in H. volcanii. The plasmids feature the tryptophan-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
220
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(220 citation statements)
references
References 41 publications
0
220
0
Order By: Relevance
“…These large differences presumably explain why no recombinant expression of the alcohol dehydrogenase ADH/D1 was observed in E. coli. The engineered H. volcanii expression system (Allers 2010 ;Allers et al 2004Allers et al , 2010 was capable of producing moderate amounts of protein in shaker-flask cultures, the essential step for the biotechnological use of halophilic enzymes remains a large-scale production in bioreactors. The method established in this study facilitates straightforward batch cultivation of H. volcanii H1895 in a stirred-tank bioreactor using optimised settings and media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These large differences presumably explain why no recombinant expression of the alcohol dehydrogenase ADH/D1 was observed in E. coli. The engineered H. volcanii expression system (Allers 2010 ;Allers et al 2004Allers et al , 2010 was capable of producing moderate amounts of protein in shaker-flask cultures, the essential step for the biotechnological use of halophilic enzymes remains a large-scale production in bioreactors. The method established in this study facilitates straightforward batch cultivation of H. volcanii H1895 in a stirred-tank bioreactor using optimised settings and media.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several strategies have been applied to engineer H. volcanii for improving heterologous gene expression resulting in the H1424 strain (Allers 2010 ;Allers et al 2010 ). The corresponding plasmid to this strain is pTA963 with the inducible tryptophanase promoter p.tna, allowing the induction of intracellular protein overexpression by L-tryptophan (Allers 2010 ;Allers et al 2004Allers et al , 2010Bitan-Banin et al 2003 ;Large et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, as found in type-II AAA+ enzymes, the homohexameric Cdc48 motor in the recently discovered archaeal Cdc48·20S proteasome contains two AAA+ modules (7,8). Cdc48 is essential in archaea and eukaryotes, and structural studies of a mouse ortholog have shown that its AAA+ modules are organized into discrete D1 and D2 rings (9)(10)(11). Cdc48 also contains a family-specific N domain, as well as a flexible C-terminal sequence, including an HbYX (hydrophobic, tyrosine, any residue) tripeptide important for 20S binding, which is similar to motifs in Mpa/Arc, Pan, and Rpt 1-6 (8).…”
mentioning
confidence: 99%
“…Notably, deletion mutants can be constructed very easily, 32,33 it can be grown in microtiter plates enabling phenotyping of mutants, 31 transcriptome analysis using DNA microarrays has been established, 34,35 proteome analysis is routinely performed, 36,37 and many molecular genetic tools are available. [38][39][40] Here we report the application of two bioinformatic approaches to predict sRNA genes in the genome in H. volcanii by comparative genomics of intergenic regions. In addition, (differential) expression of the predicted putative sRNA genes was characterized by DNA microarray analysis and by comparison with the results of high throughput sequencing performed in a parallel study.…”
Section: Introductionmentioning
confidence: 99%